The Effect of Indirect Compensation on Employee Performance in Daluman Villa Kuta Bali - Sri Sukmawati Wijaya; I Ketut Surata; Luh Putu Kartini; Raissa Puspita (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
During the pandemic situation, take interest to indirect compensation in order to maintain employee performance becomes very important while increasing direct compensation will be difficult. The purpose of this study is to find out the significance effect of indirect compensation toward employee performance based on criteria of Byars and Rue’ indirect compensation model and Sedarmayanti’s employee performance model. Mixed method is chosen in this research to study the employee perception of Daluman Vila using questionnaire with census method and elaborate it with interview result. The quantitative data is then analyzed using simple regression test, meanwhile the qualitative data is analyzed using descriptive analysis and triangulation. The result shows that employees supporting facilities in indirect compensation criteria, and initiative in employee performance, obtained lowest score. To improve these aspects, evaluation related to supporting employee facilities and designing employee performance indicator for Daluman Villa personal use are suggested to be done.